Field notes for a Peregrine Falcon sighting by Tim Dwyer, May 10 1981 - Dwyer, Timothy L.et al (1981)
Field notes written by Tim Dwyer giving details of a Peregrine Falcon sighting at the Cedar River bridge on Iowa Highway 22 in Muscatine County, IA on May 3, 1981. Epson - sheet feed